Arbuscular mycorrhizal fungus alleviates anthracnose disease in tea seedlings - Chen, Weili; Ye, Tao; Sun, Qinyu; Niu, Tingting; Zhang, Jiaxia (Frontiers in Plant Science, 2023)
Tea gains increasingly popularity all over the world in recent years, and its yield and quality depend on the growth and development of tea plants (Camellia sinensis (L.) Kuntze) in various environments. Nowadays, biotic stress and extreme weather, such as high temperature, drought, waterlogging, pests and diseases, bring about much pressure on the production of tea with high quality. Wherein, anthracnose, which is the most common and serious disease of tea plant, has earned more and more attention as its control mainly relies on chemical pesticides. Arbuscular mycorrhizal fungi (AMF), forming symbiosis with most terrestrial plants, participate in plant resistance against the anthracnose disease, which was found by previous studies in a few herbaceous plants. However, there are few researches about AM fungal regulation on resistance to the anthracnose pathogen in woody plants so far. In this paper, we investigated effect of AMF on the development of anthracnose caused by Colletotrichum camelliae and tried to decipher the pertinent mechanism through transcriptome analysis. Results showed that inoculating AMF significantly reduced the damage of anthracnose on tea seedlings with reducing the lesion area by 35.29% compared to the control. Content of superoxidase anion and activities of catalase and peroxidase significantly increased (P < 0.05) in mycorrhizal treatment in response to the pathogen with 1.23, 2.00 and 1.39 times higher, respectively, than those in control. Pathways of plant hormone signal transduction, MAPK signaling and phenylpropanoid biosynthesis might play roles in this regulation according to the transcriptomic results. Further RDA (Redundancy analysis) and PLS-SEM (Partial least squares structural equation modeling) analysis found that plant hormone, like auxin and ethylene, and antioxidant system (especially peroxidase) were of a great importance in the AM fungal alleviation of the anthracnose. Our results preliminarily indicated the mechanisms of enhanced resistance in mycorrhizal tea seedlings to the anthracnose pathogen, and provided a theoretical foundation for application of AMF as one of biological control methods in tea plantation.